Rancang Bangun Sistem Penghematan Energi Listrik menggunakan Komunikasi Bluetooth Low Energy dan WiFi berbasis Cloud Server Blynk - Muchtar Ardhiansyah; Mochammad Hannats Hanafi Ichsan; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The use of electricity is a basic requirement for humans today, therefore it is necessary to have savings in its use so that lower costs and the supply of electrical energy in an area can be saved for something unexpected. Internet of Things is a device or system that is connected and communicates in an internet network. By using IoT, we can carry out a long distance communication which makes the performance of a system more effective and efficient. The communication module that is quite popular in IoT is Bluetooth Low Energy (BLE), but in BLE there are still drawbacks, namely the inability to connect to the internet so that a gateway is needed to communicate with the cloud server. This study aims to design an electrical energy saving system. The results of this study indicate that the system can work well. The delay obtained from sending data at the gateway to the Blynk Cloud Server has an average delay of 1,930 s with a jitter of 0.754 s, the average delay from the sensor node to the gateway is 0.672 s. The next test used a variation scenario of 1 meter - 11 meter distance with uccess ratio parameter. The highest success ratio is 90% at a distance of 1 meter and the lowest success ratio is 0% at a distance of 11 meters. The saving of electrical energy is up to 59.04%.